2015
DOI: 10.1159/000438593
|View full text |Cite
|
Sign up to set email alerts
|

Isocitrate Dehydrogenase 2 Suppresses the Invasion of Hepatocellular Carcinoma Cells via Matrix Metalloproteinase 9

Abstract: Background/Aims: Isocitrate dehydrogenase 2 (IDH2) is a mitochondrial NADP-dependent isocitrate dehydrogenase, and has been found to be a tumor suppressor in several types of tumors. However, the roles of IDH2 in hepatocellular carcinoma (HCC) as well as underlying mechanisms remain unknown. Methods: The IDH2 and matrix metalloproteinase 9 (MMP9) levels in the specimens from 24 HCC patients were investigated by Western blot and ELISA, respectively. Their relationship was examined by correlation analyses. Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 36 publications
(44 reference statements)
1
17
0
Order By: Relevance
“…In agreement with our results, Chen et al found that re-expression of PRSS8 up-regulated E-cadherin expression in human transitional cell carcinomas KU-7 cells [8]. Another protein, MMP9, can degrade extracellular matrix components and thus, promote the invasion of tumour cells [17,18], and was also reduced in parallel with the upregulation of PRSS8. This suggests that PRSS8 may inhibit the metastasis and invasion of HCC through a switch from N-cadherin to E-cadherin expression, and the downregulation of MMP9.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with our results, Chen et al found that re-expression of PRSS8 up-regulated E-cadherin expression in human transitional cell carcinomas KU-7 cells [8]. Another protein, MMP9, can degrade extracellular matrix components and thus, promote the invasion of tumour cells [17,18], and was also reduced in parallel with the upregulation of PRSS8. This suggests that PRSS8 may inhibit the metastasis and invasion of HCC through a switch from N-cadherin to E-cadherin expression, and the downregulation of MMP9.…”
Section: Discussionsupporting
confidence: 92%
“…It is thought that the effect of IDH2 expression on neoplastic progression and drug resistance differs with respect to the site of origin and histological type. [50][51][52][53][54][55] Our study suggests the hypothesis that inhibition of wild-type IDH2 may have therapeutic potentials, regardless of IDH2 expression levels. Concordantly, we excluded that the IDH2 mutational status or its aberrant expression was associated to PI responsiveness in MM cells.…”
Section: Discussionmentioning
confidence: 61%
“…With regard to the six verified downregulated proteins, IDH2 is a mitochondrial NADP-dependent isocitrate dehydrogenase that functions variably in different types of cancer. It has been reported that IDH2 inhibited the invasion of hepatocellular carcinoma cells via the regulation of MMP9, and therefore acted as a tumor suppressor (47). By contrast, in another study the overexpression of IDH2 promoted cell growth in colon cancer (48).…”
Section: Discussionmentioning
confidence: 89%